FEATURES OF PHYSICAL DEVELOPMENT OF SENIOR PRESCHOOL CHILDREN (Modern American Journal of Medical and Health Sciences, 2025)
Currently, many scientists and specialists are raising the issue of the need for a significant restructuring of the system of physical education for preschool children. The period of adaptation to the beginning of systematic schooling is one of the most difficult for a child. Successful adaptation and subsequent schooling largely depend on health and the readiness of the body's physiological systems to withstand the constant impact of academic demands. It is known that when assessing a child's readiness for school, primary consideration has been given to the development of school- relevant psychophysiological functions (attention, memory, thinking, etc.). Equally important is the child's level of physical readiness for school, as systematic schooling places increased static loads on the body associated with the need to maintain a working posture for extended periods while sitting at a student's desk. Unfortunately, many hygienists have recently noted a decline in the functional capabilities of today's older preschoolers, including their level of physical fitness.